Balance Function Assessment and Management : Third Edition. - Jacobson, Gary P. (Plural Publishing, Incorporated, 2019)
The third edition of Balance Function Assessment and Management, the leading textbook on the subject, continues to comprehensively address the assessment and treatment of balance system impairments through contributions from top experts in the areas of dizziness and vertigo. Designed for use in graduate audiology programs and by practicing audiologists, this is also a valuable text for those in the fields of physical therapy, otolaryngology, and neurology.